Colonic epithelial mTORC1 promotes ulcerative colitis through COX-2-mediated Th17 responses. Issue 6 (November 2018) - Lin, Xiaojun; Sun, Qiuyi; Zhou, Ling; He, Minhong; Dong, Xiaoying; Lai, Mingqiang; Liu, Miao; Su, Yongchun; Jia, Chunhong; Han, Zelong; Liu, Side; Zheng, Hang; et al.
Abstract The functional role of colonic epithelium in the pathogenesis of ulcerative colitis (UC) remains unclear. Here, we reveal a novel mechanism by which colonic epithelia recruit T helper-17 (Th17) cells during the onset of UC. mTOR complex 1 (mTORC1) was hyper-activated in colonic epithelia of UC mice. While colonic epithelial TSC1 (mTORC1 negative regulator) disruption induced constitutive mTORC1 activation in the colon epithelia and aggravated UC, RPTOR (essential mTORC1 component) depletion inactivated mTORC1 and ameliorated UC. TSC1 deficiency enhanced, whereas RPTOR ablation reduced the expression of cyclooxygenase 2 (COX-2), interleukin-1 (IL-1), IL-6, and IL-23, as well as Th17 infiltration in the colon. Importantly, inhibition of COX-2 reversed the elevation in the expression of these proinflammatory mediators induced by TSC1 deficiency, and subsequently reduced the symptoms and pathological characteristics of UC in mouse models. Mechanistically, mTORC1 activates COX-2 transcription via phosphorylating STAT3 and enhancing it's binding to the COX-2 promoter. Consistently, enhanced mTORC1 activity and COX2 expression, as well as strong positive correlation between each other, were observed in colonic epithelial tissues of UC patients. Collectively, our study demonstrates an essential role of epithelial mTORC1 in UC pathogenesis and establishes a novel link between colonic epithelium, Th17 responses, and UC development.